"Empowering independence: the role of occupational therapy in overcoming life challenges" - Sadia Saleem; Khadija Saleem; Sabeen Masood; Faiza Yousaf; Laiba Saleem (Journal of the Pakistan Medical Association, 2025)
Occupational Therapist promote functional independence and achievement of life goals. Occupational Therapy means to make the patient independent in activities of daily living (ADLs) according to patient potential. Occupational therapy practitioners help the patient to participate in daily activities and increase their participation and independence. Occupational therapist help people of all ages to participate in the things they want and need to do through the therapeutic use of everyday activities. In all of their environment home, work, school and community occupational therapist helps people through engagement in occupation that addresses the cognitive, physical and psychological aspects of their well- being. 1 To manage the challenges of delayed milestones, Autism, Attention Deficit Hyperactive Disorder, childhood obesity and other conditions after injury, Occupational Therapist helps children to develop skills in the areas of school, play, and self care. These are seen as child’s main and important areas of occupation. Occupational therapist enable the children to achieve their self esteem, maximum potential, general well being and social skills by supporting the children. 2 Occupational Therapists are instrumental in providing early Intervention for a variety of disorders including Developmental coordination disorder, Developmental delay, Learning difficulties, Dyspraxia, Autistic spectrum disorder, Sensory processing difficulties, Attention deficit hyperactive disorder, Visual perception deficit, in all these disorders occupational therapist work with Handwriting development, Self- care and Social skills, Learning ( develop creativity and imagination through toys and play) . 3 The occupational therapist Addresses following Physical, Developmental & Cognitive Disabilities. 4. Modifying environments Providing adaptive equipment Creating options for play Addressing social skills Alleviates sensory challenges. In Adults, to carry out daily living activities the aim of occupational therapy is to facilitate individuals in the key areas of work, leisure that are meaningful to them. After stroke, surgery or other following medical incidents rehabilitation is provided by occupational therapist to resume function. Spinal cord injuries Multiple Sclerosis Traumatic brain injury Stroke Burns Among older adults, such as dementia enhance well being and overall health and decrease depression and anxiety. Provide rehabilitation and adaptive devices. By providing emotional support and encouragement we minimize the risk of falling by assisting the older adults with balance, posture and safety techniques. —Continue